Micromechanics modeling of moisture diffusion in woven composites - Tang, X.; Whitcomb, J.D.; Li, Y.; Sue, H-J
Woven composite structures are expected to experience a range of hygrothermal environmental conditions during their service life. Since moisture can cause plasticization of the polymer matrix, alter the stress state and degrade the fiber/matrix interface, understanding of moisture absorption and desorption behavior is critical for predicting long-term material and structural performance. This paper focuses on the effect of weave microstructure on the moisture diffusion behavior of polymer matrix woven composites. The effect of tow architectural parameters on the through-the-thickness moisture diffusion behavior is investigated using finite element subcell models with appropriate boundary conditions. The results are presented and discussed in terms of the tow waviness, tow cross-section shape and weave pattern. Simulations of moisture diffusion tests are also conducted for 3-ply woven hybrid composite laminates consisting of uni-weave and 4-harness satin weave, in which the tow fiber volume fractions are determined from image analysis. The results from the simulation are in good agreement with the available test results.
Keywords: A. TEXTILE COMPOSITE; B. HYGROTHERMAL EFFECT; C. FINITE ELEMENT ANALYSIS; MOISTURE DIFFUSION